DIVERSIFIKASI PANGAN OLAHAN JAGUNG SEBAGAI UPAYA PENGEMBANGAN AGROINDUSTRI DIMASA PANDEMI COVID-19 DI DESA BRUMBUNG DEMAK JAWA TENGAH - Eny Priyanti; Niyar Chandra Agustin; Sri Subekti (Dinamika Journal : Pengabdian Masyarakat, 2021)
Currently, Indonesia is experiencing a pandemic period caused by the spread of the Covid-19 virus, resulting in the decline of the economy from all fields, so as an effort to help the community, community service activities are held that aim to increase community productivity through the development of agro-industry owned by Brumbung village, Demak Regency, Central Java by introducing and practice how to process so that it becomes a quality product so that it can increase the income of the village community. Corn is one type of agro-industry that is the leading potential of Brumbung Demak village, Central Java, corn is a plant that has high nutritional content and can be used as a substitute for rice because it contains carbohydrates, so it can be developed by diversification into processed foods that have added value both in terms of nutrition , taste, form and commercial value. The method used in this community service activity is in the form of counseling, practice and assistance on how to process corn into processed food, namely crispy and hygienic corn crackers as an effort to increase income and sustainable community welfare.